2012
DOI: 10.1016/j.virusres.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of host genetic diversity and viral entry as sources of between-host variation in viral load

Abstract: Little is known about the factors that drive the high levels of between-host variation in pathogen burden that are frequently observed in viral infections. Here, two factors thought to impact viral load variability, host genetic diversity and stochastic processes linked with viral entry into the host, were examined. This work was conducted with the aquatic vertebrate virus, Infectious hematopoietic necrosis virus (IHNV), in its natural host, rainbow trout. It was found that in controlled in vivo infections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
2
9
1
Order By: Relevance
“…None of the IHNV genotypes used for coinfection studies demonstrated a significant reduction in replication in simultaneous coinfection competition compared to single-infection controls (19,36). This was observed even though fish in coinfection groups were initially challenged with twice the total virus compared to fish in single-infection groups, and total measured viral load was, at times, doubled in coinfected fish compared to that in singly infected fish (19,20).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…None of the IHNV genotypes used for coinfection studies demonstrated a significant reduction in replication in simultaneous coinfection competition compared to single-infection controls (19,36). This was observed even though fish in coinfection groups were initially challenged with twice the total virus compared to fish in single-infection groups, and total measured viral load was, at times, doubled in coinfected fish compared to that in singly infected fish (19,20).…”
Section: Discussionmentioning
confidence: 95%
“…However, direct competition within the host seems unlikely in our system when considering results from in vivo coinfection studies previously performed using these same IHNV genotype pairs (17,19,20,36). None of the IHNV genotypes used for coinfection studies demonstrated a significant reduction in replication in simultaneous coinfection competition compared to single-infection controls (19,36).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations